2013
DOI: 10.1242/jcs.140673
|View full text |Cite
|
Sign up to set email alerts
|

The molecular basis for selective assembly of the UBAP1-containing, endosome-specific ESCRT-I complex

Abstract: ESCRT-I is essential for the multivesicular body (MVB) sorting of ubiquitylated cargo such as epidermal growth factor receptor, as well as for several cellular functions, such as cell division and retroviral budding. ESCRT-I has four subunits; TSG101, VPS28, VPS37 and MVB12. There are several members of VPS37 and MVB12 families in mammalian cells, and their differential incorporation into ESCRT-I could provide function-specific variants of the complex. However, it remains unclear whether these different forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 59 publications
(149 reference statements)
5
31
0
Order By: Relevance
“…In contrast, HD-PTP function is largely restricted to the early endosome (Doyotte et al., 2008, Parkinson et al., 2015) where it acts in close cooperation with ESCRT-0 (Ali et al., 2013) and UBAP1 (ESCRT-I) to downregulate multiple ubiquitinated cargoes (Agromayor et al., 2012, Kharitidi et al., 2015). UBAP1 is an ubiquitin-binding ESCRT-I subunit that acts exclusively in MVB sorting (Stefani et al., 2011, Wunderley et al., 2014) and, like for HD-PTP (Cheng et al., 1998, Toyooka et al., 2000), haploinsufficiency of UBAP1 is linked to nasopharyngeal carcinoma (Qian et al., 2001). UBAP1 is also a risk factor for familial frontotemporal lobar degeneration (Rollinson et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, HD-PTP function is largely restricted to the early endosome (Doyotte et al., 2008, Parkinson et al., 2015) where it acts in close cooperation with ESCRT-0 (Ali et al., 2013) and UBAP1 (ESCRT-I) to downregulate multiple ubiquitinated cargoes (Agromayor et al., 2012, Kharitidi et al., 2015). UBAP1 is an ubiquitin-binding ESCRT-I subunit that acts exclusively in MVB sorting (Stefani et al., 2011, Wunderley et al., 2014) and, like for HD-PTP (Cheng et al., 1998, Toyooka et al., 2000), haploinsufficiency of UBAP1 is linked to nasopharyngeal carcinoma (Qian et al., 2001). UBAP1 is also a risk factor for familial frontotemporal lobar degeneration (Rollinson et al., 2009).…”
Section: Introductionmentioning
confidence: 99%
“…It is a component of the endosome‐specific endosomal sorting complexes required for transport‐I (ESCRT‐I) complex that functions to sort ubiquitylated cargo such as epidermal growth factor receptor to the multivesicular body (MVB) and for endosomal ubiquitin homeostasis (Stefani et al, ). There are two functionally critical domains in UBAP1—the UMA (UBAP1‐MVB12‐associated) domain for ESCRT‐I binding near the N‐terminus (de Souza & Aravind, ; Wunderley, Brownhill, Stefani, Tabernero, & Woodman, ), and the solenoid of overlapping ubiquitin‐associated (SOUBA) domains for ubiquitin interaction near the C‐terminus (Agromayor et al, ; Figure a). The two predicted truncated proteins reported in this study and all proteins reported by Farazi Fard et al have an intact UMA domain while lacking the SOUBA domains.…”
Section: Discussionmentioning
confidence: 99%
“…We speculated that the type and magnitude of transcriptional responses after individual and concurrent silencing of VPS37 paralogs might be attributed to distinct ESCRT-I stability. It was previously shown that knockdown of some ESCRT-I core components induced partial or complete degradation of other complex subunits (Stefani et al, 2011;Wunderley et al, 2014); yet, a detailed characterization of all ESCRT-I subunits after individual and concurrent Vps37 proteins depletion has not been performed so far.…”
Section: Escrt-i Is Destabilized After Either Concurrent Depletion Ofmentioning
confidence: 99%
“…ESCRT-I is a heterotetramer composed of three core components (Tsg101, Vps28 and one of four Vps37 family members) and a single auxiliary protein (UBAP-1, Mvb12A or Mvb12B) (Stefani et al, 2011;Wunderley et al, 2014). At least under some conditions two of its subunits (Tsg101 and Vps37A) have been identified as putative tumor suppressors (Li and Cohen, 1996;Moberg et al, 2005;Xu et al, 2003).…”
Section: Introductionmentioning
confidence: 99%